AC ripple loss analysis of a novel composite energy pipeline - Lina Wang (Elsevier, 2022)
A novel composite high-temperature superconducting (HTS) energy pipeline integrated with power cable and liquid hydrogen (LH2) and liquefied natural gas (LNG) is proposed in this paper. AC ripple loss will deteriorate energy transmission efficiency and increase load of the HTS cooling system, and therefore is a key parameter. This work has originally explored a novel composite pipeline having three different kinds of energy integrated and characteristics of AC ripple loss under the entire pipeline. Electromagnetic-thermal coupling model is established. Dependence of AC ripple loss on structure, frequency, current and AC ripple component is analyzed. Results provide a theoretical base for the optimization of composite HTS energy pipeline system.